Perbandingan Pendapatan Petani Kacang Tanah Di Desa Tombasian Atas Kecamatan Kawangkoan Barat Kabupaten Minahasa (Studi kasus : Kelompok tani yang mengikuti dan yang tidak mengikuti penyuluhan pertanian). - Aling Eliana; Eyverson Ruauw; Oktavianus Porajow; Maya H. Montolalu (Universitas Sam Ratulangi, 2015)
ABSTRACT This research was carried on in the village of Upper Tombasian Kawangkoan Western District of Minahasa. The method used in this research is survey method. The data used in this study are primary data and secondary data. Primary data were obtained using the technique of direct interview to the respondents using a questionnaire (questionnaire) as a tool in data collection. As for the secondary data obtained from agencies associated with this research. Analysis of the data used in this research is descriptive analysis and the final results are presented using tables. Addressing the results of this study that the average income of peanut farmers who follow agricultural extension greater than the farmers who do not follow the agricultural extension. Income level peanut farmers who follow agricultural extension Rp. 30.7655 million. While the income levels of farmers who do not follow the agricultural extension Rp. 12.627 million. The difference is due to the income of farmers who follow agricultural extension receive fee waivers in the procurement of inputs, particularly fertilizer use is managed to increase productivity yields and managed to increase the total income of farmers who follow agricultural extension. Â Keywords: Farmers Group, Peanut, Agricultural Extension and Revenue